Pengaruh Kompleksitas Operasi, Ukuran Perusahaan dan Komite Audit terhadap Kualitas Audit dengan Audit Delay sebagai Moderasi - Febria Amanda; David Pangaribuan; Panata Bangar Hasioan Sianipar (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study aims to examine the influence of Operational Complexity, Company Size, and Audit Committee on Audit Quality with Audit Delay as a moderating variable. The population in this research consists of all banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sampling technique used was the purposive sampling method and obtained 47 company samples. The analysis methods used were Descriptive Statistical Analysis, Logistic Regression Analysis, Hypothesis Testing and Moderation Regression Analysis. The results of this study indicate that partially Complexity Operational and Audit Committe has a positive effect on Audit Quality and the variables Company Size do not affect Audit Quality. The results of the study for the moderating variable, namely Audit Delay, are able to moderate (weaken) the positive effect of Audit Committe on Audit Quality and Audit Delay is unable to moderate Complexity Operational and Company Size.